SOCIOCULTURAL SELF-ORGANIZATION AND PROFESSIONAL ETHICS OF THE ZEMSTVO INTELLIGENTSIA IN THE DONETSK REGION (1860s – 1917) - Saraieva, Olha; Saraieva, Mariia (Young Scholars Grinchenko – Seton International Journal, 2026)
The article is devoted to the study of the activities of local self-government bodies of the Donetsk region at the turn of the 19th – 20th centuries, which acted as strategic agents of the region’s comprehensive modernization. Particular attention is paid to the fact that the main instrument of these transformations was the zemstvo intelligentsia – the so-called "third element" (teachers, doctors, agronomists, statisticians), whose everyday activity depended not only on the level of professional training but also on the degree of their social protection. It is emphasized that the introduction by the zemstvos of innovative mechanisms of social insurance, housing autonomy, and corporate solidarity for their time made it possible to form a stable regional elite capable of resisting the destructive influences of society’s radicalization and marginalization. It is noted that the experience of the zemstvos is useful in the conditions of the formation of today’s civil society.